Sedentary Lifestyle and Nutritional Status Among Adolescents: A Cross-Sectional Study in Bogor City - Laesa Wira Liesma Djati; Asri Ismiyani Nurlita; Deannisa Fajriaty (Media Publikasi Cendekia Indonesia, 2026)
Nutritional problems in Indonesia remain unresolved, especially among adolescents who experience the triple burden of malnutrition, namely undernutrition, overweight, and micronutrient deficiency. Adolescents in Indonesia are increasingly adopting a sedentary lifestyle, which is characterized by prolonged screen time and low levels of daily physical activity. The objective of this study was to analyze the relationship between a sedentary lifestyle and nutritional status among adolescents at Al-Ghazaly High School in Bogor City. This observational cross-sectional study involved 50 adolescents aged 15 – 18 years selected through purposive sampling based on inclusion and exclusion criteria. Primary data on subject characteristics and sedentary lifestyles were collected using the 7 Days-Adolescent Sedentary Activity Questionnaire (ASAQ) while nutritional status was assessed based on anthropometric measurements using BMI/A z-scores. Spearman's correlation was used for data analysis. The findings indicated that the subjects were categorized as having a moderate level of sedentary behavior with the highest average daily time spent on sedentary activities involving the use of computers or mobile phones for gaming, social media, and other similar activities (295 minutes/day). The majority of subjects had a normal nutritional status. Based on the correlation analysis, there was no significant relationship between sedentary lifestyle and nutritional status (p = 0.756), indicating a very weak positive correlation (r = 0.045). To promote better health, it is recommended that adolescents engage in active breaks between classes and limit excessive use of mobile phones. Future researchers should use a larger sample size and include other variables such as nutritional knowledge and family characteristics.